Vascular Inflammation and Endothelial Dysfunction in Experimental Hypertension - Carmine Savoia; Lidia Sada; Luigi Zezza; Lorenzo Pucci; Francesco Maria Lauri; Alberto Befani; Alessandro Alonzo; Massimo Volpe (International Journal of Hypertension)
Essential hypertension is characterized by increased peripheral vascular resistance to blood flow. The endothelium is a crucial regulator of vascular tone. Its function is impaired in patients with hypertension, with reduced vasodilation, increased vascular tone associated with a proinflammatory and prothrombotic state. Low-grade inflammation localized in vascular tissue is therefore recognized as an important contributor to the pathophysiology of hypertension, to the initiation and progression of atherosclerosis as well as to the development of cardiovascular diseases.